Differential suppression of rice weeds by allelopathic plant aqueous extracts - Khaliq,A (2013)
Herbicidal potential of different plant aqueous extracts was evaluated against early seedling growth of rice weeds in pot studies. Plant aqueous extracts of sorghum (Sorghum bicolor), sunflower (Helianthus annuus), brassica (Brassica compestris), mulberry (Morris alba), eucalyptus (Eucalyptus camaldunensis), and winter cherry (Withania somnifera) at a spray volume of 18 L ha-1 each at the 2-4 leaf stage of rice weeds viz horse purslane (Trianthema portulacastrum) [broad-leaf], jungle rice (Echinochloa colona), and E. crus-galli (barnyard grass) [grasses] and purple nut sedge (Cyperus rotundus) and rice flat sedge (C. iria) [sedges]. The results showed significant interactive effects between plant aqueous extracts and the tested weed species for seedling growth attributes depicting that allelopathic inhibition was species-specific. Shoot and root length, lateral plant spread, biomass accumulation, and leaf chlorophyll contents in test species were all reduced by different extracts. The study suggested the suppressive potential of allelopathic plant aqueous extracts against rice weeds, and offered promise for their usefulness as a tool for weed management under field conditions.